Work-related mobile internet usage during off-job time and quality of life: The role of work family conflict and off-job control - Elshaer, Ibrahim Abdelhamid; Azazz, Alaa Mohamed Shaker; Fayyad, Sameh (International Journal of Innovative Research and Scientific Studies, 2024)
The unexpected outbreak of the COVID-19 pandemic brought unprecedented challenges to various aspects of society, including education and work practices. Although tremendous progress has been achieved in reducing the severe impact of COVID-19 on education, its repercussions are still apparent in behaviours connected to the workplace and people’s views of their general quality of life (QOL). In this research paper, we investigate the relationship between work-related mobile internet usage during off-job time and quality of life considering the mediating effect of work-family conflict and the moderating effect of off-job control. Data were collected from 341 faculty members and the obtained data was analyzed by Smart PLS structural equation modeling (PLS-SEM) using a cross-sectional research design. The study findings reveal that both work-related smartphone use during off-job hours and work-family conflict significantly and negatively impact the quality of life of faculty members. Moreover, the study identified that individuals with greater perceived off-job control demonstrated better quality of life outcomes despite the challenges posed by work-related smartphone use. The results of this study contribute to the understanding of the implications of COVID-19 on work practices and personal well-being. Given the growing reliance on smartphones and digital connectivity in the post-pandemic era, it underscores the importance of recognizing the boundaries between work and personal life. Additionally, it highlights the need for employers and policymakers to establish policies and interventions that promote off-job control enabling individuals to disengage from work-related demands during non-work hours effectively.